2021
DOI: 10.1371/journal.pone.0246491
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of a nektobenthic community exploited by a multispecific bottom trawling fishery in Northeastern Brazil

Abstract: We used complementary stable isotope (SIA) and stomach content (SCA) analyses to investigate feeding relationships among species of the nektobenthic communities and the potential ecological effects of the bottom trawling of a coastal ecosystem in northeastern Brazil. Carbon (δ13C) and nitrogen (δ15N) compositions were determined for five basal sources and 28 consumers, from zooplankton to shrimp and fish species. Fishes and basal sources showed a broad range of δ15N (fishes: 6.49–14.94‰; sources: 2.58–6.79‰) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…These authors observed distinct feeding preferences between species, A. clupeoides being a piscivorous one, H. clupeola showing a phytoplanktonic preference in its diet, and A. tricolor together with O. oglinum a zooplanktonic preference. These differences in feeding habit between the species corroborate with literature, as they are reported to belong to distinct trophic guilds (Mai & Vieira, 2013;Andrade-Tubino et al, 2019;Favero et al, 2019;Lira et al, 2021) coupled with differences in ecomorphological attributes which possibly contribute to their coexistence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These authors observed distinct feeding preferences between species, A. clupeoides being a piscivorous one, H. clupeola showing a phytoplanktonic preference in its diet, and A. tricolor together with O. oglinum a zooplanktonic preference. These differences in feeding habit between the species corroborate with literature, as they are reported to belong to distinct trophic guilds (Mai & Vieira, 2013;Andrade-Tubino et al, 2019;Favero et al, 2019;Lira et al, 2021) coupled with differences in ecomorphological attributes which possibly contribute to their coexistence.…”
Section: Discussionsupporting
confidence: 89%
“…To evaluate eventual correlations between morphological similarities, the species and feeding were classified into the following trophic guilds: carnivore first order (Favero et al, 2019): individuals that feed primarily of benthic invertebrates; carnivore second order (Favero et al, 2019): fish with the diet based on invertebrates which may occasionally consume fish; planktivore (Favero et al, 2019): species that feed predominantly on phytoplankton occasionally also feeding on zooplankton; zoobenthivore (Elliott et al, 2007): fish species that feed predominantly on invertebrates associated with the substrate, specially animals that live just above the sediment; and zooplanktivore (Elliott et al, 2007): fish species with diet predominantly composed by zooplankton, such as planktonic crustaceans and fish eggs and larvae. Species feeding guilds classification was based on literature (Mai & Vieira, 2013;Andrade-Tubino et al, 2019;Favero et al, 2019;Lira et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Functional guild: ES, estuarine species; MM, marine migrants; MS, marine stragglers; Trophic guild: HV, herbivore; DV, detritivore; OV, omnivore; PV, piscivore; ZB, zoobenthivore; ZP, zooplanktivore; IR, relative importance based on the abundance and frequency of species: 1, abundant and frequent; 2, abundant and infrequent; 4, less abundant and infrequent. *Ecological role information obtained by (Ferreira et al, 2019); (Lira et al, 2021b); (Gonzalez et al, 2019). **Economic role information obtained by (ESTATPESCA, 2006;Lira et al, 2010…”
Section: Data Collectionmentioning
confidence: 99%
“…However, studies characterising the functioning of tropical coastal ecosystems are scarce. Except for the studies published by Lira et al (2021b) and (Pereira et al, 2020), those available are monospecific (Gonzalez et al, 2019;Soares et al 2020, Pelage et al 2021 or only focus on the relative importance of basal food sources to macroconsumers (Claudino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%